The left prefrontal cortex supports inhibitory processing during semantic memory retrieval. (January 2021) - Marko, Martin; Riečanský, Igor
Abstract: Semantic control refers to a set of neural and cognitive mechanisms that govern semantic processing and retrieval. Neuroimaging studies have indicated that controlled semantic processing engages the left prefrontal cortex (PFC), yet the functional role of the prefrontal activity in semantic control is poorly understood and was therefore addressed in the present study. We used a double-blind randomized controlled experiment, in which participants from three distinct groups received anodal transcranial direct current stimulation (tDCS) over left lateral PFC ( n  = 40), a control tDCS over temporoparietal cortex ( n  = 40), or sham stimulation ( n  = 41), while executing automatic and controlled semantic retrieval tasks as well as additional control tasks assessing working memory and semantic judgement. We demonstrate that anodal tDCS of the left lateral PFC improved inhibition of prepotent semantic associations but had no significant effect on retrieval of habitual associates or switching between retrieval rules. The prefrontal tDCS also enhanced working memory capacity, but this effect did not account for the improved semantic inhibition. The control temporoparietal tDCS did not affect semantic retrieval. Our findings show that semantic inhibition and switching represent distinct components of the semantic control system and indicate that the left lateral PFC is involved in a filtering process that constrains the accessible semantic representations (i.e., a proactive pre-retrieval inhibition) or suppresses already retrieved responses (i.e., a retroactive post-retrieval inhibition). The recognition of such an inhibitory process could inspire novel treatments targeting altered semantic processing.